Impact of PEGylation and hyaluronan functionalization on lipoplex-mediated mRNA delivery to the canine retina - Tatyana Appelbaum; David A. Smith; Kei Takahashi; Jennifer C. Kwok; Hannah Sorenson; William A. Beltran (Drug Delivery)
Efficient messenger ribonucleic acid (mRNA) delivery to the retina remains challenging. This study investigated the effects of various polyethylene glycol (PEG) derivatives on the stability and uptake of cationic lipid-based mRNA lipoplexes in vitro and assessed the delivery of selected formulations to the canine retina. We present an optimized workflow for formulating mRNA lipoplexes in pure water, achieving high encapsulation efficiency. PEGylation enhanced stability of lipoplexes, particularly with PEG-DMG or hyaluronan conjugated to PEG-DPPE (HA-PEG-DPPE), maintaining size and zeta potential for 48 hours. RNA in situ hybridization (RNA-ISH) confirmed efficient internalization of PEGylated mRNA lipoplexes by cultured RAW264.7 and ARPE19 cells, though corresponding protein expression varied between cell lines. Analysis at 24 hours post-intravitreal injection of PEG-DMG- and HA-PEG-DPPE-stabilized enhanced green fluorescent protein (eGFP) mRNA lipoplexes revealed limited mRNA accumulation in inner retinal layers. In contrast, 24 hours after their subretinal administration, eGFP mRNA was detected in all retinal cell types, including photoreceptors, with accumulation comparable to endogenous rhodopsin (RHO) mRNA levels. eGFP protein expression, though, was limited to the retinal pigment epithelium (RPE). At 72 hours post-subretinal delivery, eGFP mRNA and protein persisted in the RPE. However, a marked reduction in eGFP levels was seen in other retinal layers, displaying a patchy pattern. Similarly, eGFP protein exhibited a patchy distribution across retinal layers outside the RPE. Furthermore, distinct differences in the cell types expressing the eGFP protein were observed between the two PEGylated mRNA lipoplex formulations. The data suggest that transfection efficiency in retinal cells is influenced by both intracellular processing of mRNA lipoplexes and their uptake, with the former playing a predominant role.